ChemInform Abstract: Cinanthrenol A, an Estrogenic Steroid Containing Phenanthrene Nucleus, from a Marine Sponge Cinachyrella sp. Issue 35 (2nd September 2014) - Machida, Koshi; Abe, Takahiro; Arai, Daisuke; Okamoto, Mayumi; Shimizu, Isao; de Voogd, Nicole J.; Fusetani, Nobuhiro; Nakao, Yoichi
Abstract The isolation, structure elucidation and determination of the absolute configuration of the title compound (I) is described.